Development of Fully Immersive Virtual Reality Job Simulator - Rosmawee, Muhammad Asyraaf Syahmi; Ismail, Mohd Norasri (Applied Information Technology And Computer Science, 2023)
Virtual Reality (VR) is a technology that is computer-generated to enable interactions between users and the virtual environment. The cost of development and exclusivity of VR equipment for VR training has led to less VR job simulators games in the market. The game Inside: VR Job Simulator is designed and develop using the simulation based Virtual Reality approach to produce a fully immersive job simulation game. The users targeted for playing this game will be teenagers from age 13 to 18 years old. The game development life cycle (GDLC) is used to develop this project. The functional testing is conducted, and the usability testing has resulted a score of 82.63 which is within the acceptable range based on the System Usability Scale (SUS). Therefore, the game could be able to assist the target users in trying to familiarize themselves and learn about the designated work environment and their tasks.